Position Paper Number 1 for the Workshop “Towards Criteria of Sustainability and Social Meaningfulness in Development“: Instrumental Reason as a Hindering Factor for Meaningful Technology Design - Hofkirchner, Wolfgang and Bichler, Robert M. (tripleC: Communication, Capitalism & Critique. Open Access Journal for a Global Sustainable Information Society, 1970)
This paper is the first of a number of position papers for the workshop “Towards Criteria of Sustainability and Social Meaningfulness in Development“
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMzEyNjkvdHJpcGxlYy52N2kyLjE1Mw